Celiac disease markers in patients with liver diseases: a single center large scale screening study - Drastich, Pavel; Honsová, Eva; Lodererová, Alena; Jarešová, Marcela; Pekáriková, Aneta; Hoffmanová, Iva; Tučková, Ludmila; Tlaskalová-Hogenová, Helena; Spičák, Julius; Sánchez, Daniel (World journal of gastroenterology, 2012)
AIM: To study the coincidence of celiac disease, we tested its serological markers in patients with various liver diseases. METHODS: Large-scale screening of serum antibodies against tissue transglutaminase (tTG), and deamidated gliadin using enzyme-linked immunosorbent assay and serum antibodies against endomysium using immunohistochemistry, in patients with various liver diseases (n = 962) and patients who underwent liver transplantation (OLTx, n = 523) was performed. The expression of tTG in liver tissue samples of patients simultaneously suffering from celiac disease and from various liver diseases using immunohistochemistry was carried out. The final diagnosis of celiac disease was confirmed by histological analysis of small-intestinal biopsy. RESULTS: We found that 29 of 962 patients (3%) with liver diseases and 5 of 523 patients (0.8%) who underwent OLTx were seropositive for IgA and IgG anti-tTG antibodies. However, celiac disease was biopsy-diagnosed in 16 patients: 4 with autoimmune hepatitis type I, 3 with Wilson's disease, 3 with celiac hepatitis, 2 with primary sclerosing cholangitis, 1 with primary biliary cirrhosis, 1 with Budd-Chiari syndrome, 1 with toxic hepatitis, and 1 with non-alcoholic steatohepatitis. Unexpectedly, the highest prevalence of celiac disease was found in patients with Wilson's disease (9.7%), with which it is only rarely associated. On the other hand, no OLTx patients were diagnosed with celiac disease in our study. A pilot study of the expression of tTG in liver tissue using immunohistochemistry documented the overexpression of this molecule in endothelial cells and periportal hepatocytes of patients simultaneously suffering from celiac disease and toxic hepatitis, primary sclerosing cholangitis or autoimmune hepatitis type I. CONCLUSION: We suggest that screening for celiac disease may be beneficial not only in patients with associated liver diseases, but also in patients with Wilson's disease.
Keywords: Young Adult; Celiac Disease; Immunoglobulin G; Male; plošný screening; Autoantibodies; mladý dospělý; Adolescent; transglutaminasy; proteiny vázající GTP; Gliadin; Česká republika; protein-glutamin:amin-gama-glutamyltransferasa 2; gliadin; Adult; prevalence; biopsie; imunoglobulin G; dospělí; imunohistochemie; mužské pohlaví; senioři; Aged; Liver transplantation; celiakie; GTP-Binding Proteins; mladiství; Tissue transglutaminase; Czech Republic; Protein Glutamine gamma Glutamyltransferase 2; Celiac disease; Mass Screening; Autoimmune liver diseases; lidé; Anti-tissue transglutaminase antibodies; ženské pohlaví; játra; Immunohistochemistry; Humans; autoprotilátky; Wilson's disease; transplantace jater; Liver Transplantation; Prevalence; imunoglobulin A; prediktivní hodnota testů; Transglutaminases; Biopsy; Liver; Liver Diseases; Female; Immunoglobulin A; lidé středního věku; Predictive Value of Tests; nemoci jater; Middle Aged